2020
DOI: 10.18488/journal.1.2020.108.450.457
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Behavioural Intention towards Adoption of Digital Banking Services in Malaysia

Abstract: Digital banking will be a disruptive digital transformation to Malaysians as the country is widely regarded as cash-based society. It is unknown on the factors that could influence behavioural intention towards adoption of digital banking services among Malaysian. This research aims to investigate the relationship of core constructs such as trialability, compatibility, observability, perceived usefulness, and perceived ease of use with consumer's intention to adopt digital banking services. This will be the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…Based on the extracted scripts according to the experts, the observation log identified the importance of factors such as ease of use, usefulness, social influence, compatibility, trialability, security, and privacy data management that will determine the success of digital bank in Malaysia and help to penetrate market across different types of users, generations and geographical locations. This is consistent with the quantitative results which further convinced the researchers that the conceptual framework from the theoretical perspectives of both TAM and IDT could explain potential user's behavioral intention in the adoption of digital banking services (Tiong, 2020). Furthermore, the employment of triangulation method, particularly data collection from webinars as a source of the qualitative approach, has further enhanced the research data which was intended to be answered by the Digital Banking Study.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Based on the extracted scripts according to the experts, the observation log identified the importance of factors such as ease of use, usefulness, social influence, compatibility, trialability, security, and privacy data management that will determine the success of digital bank in Malaysia and help to penetrate market across different types of users, generations and geographical locations. This is consistent with the quantitative results which further convinced the researchers that the conceptual framework from the theoretical perspectives of both TAM and IDT could explain potential user's behavioral intention in the adoption of digital banking services (Tiong, 2020). Furthermore, the employment of triangulation method, particularly data collection from webinars as a source of the qualitative approach, has further enhanced the research data which was intended to be answered by the Digital Banking Study.…”
Section: Discussionsupporting
confidence: 77%
“…No study has addressed the use of webinar as a tool for data collection. This paper's results could enrich the data and provide additional data to verify the qualitative findings from the Digital Banking Study published previously (Tiong, 2020). Through interpretive research philosophy, this paper discusses the potential use of webinars, including the preparation, challenges, advantages, disadvantages, and limitations of the webinar as a qualitative data collection tool based on the real-time experience during the conduct of the Digital Banking Study.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…As Komlan et al (2019) found there is a significant relationship between personal innovativeness and customers' intention in mobile money services. Moreover, Tiong (2020) found that perceived compatibility and social influence positively influence customers' intention to use digital banking services among generation Y in Malaysia. An empirical study in Saudi Arabia (Noha et al, 2021) found that user conception of perceived compatibility and facilitating condition of e-payment had a significant impact on their intention to adopt epayment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If the application system is easy to use, users will feel un-intimidated to use it (Moon & Kim, 2001). Numerous studies have been conducted over the past few years and provide empirical evidence on the important impact of PEOU on intention to use, either directly or indirectly © IEOM Society International through its impact on perceived usefulness (Akturan & Tezcan, 2012;Amin, Rizal, Hamid, Pepper, & Anis, 2008;Gu, Lee, & Suh, 2009;Hanafizadeh, Behboudi, Abedini Koshksaray, & Jalilvand Shirkhani Tabar, 2012;Koenig-Lewis et al, 2010;Mawona & Mpogole, 2013;Noor, 2011;Tan, Leby, Tan, & Lau, 2016;Yu, 2012: Tiong, 2020Hossain et al, 2019;Tran, 2021). Other studies have shown that PEOU positively affects PU (Mutahar, Daud, Ramayah, Isaac, & Alrajawy, 2016).…”
Section: Perceived Ease Of Usementioning
confidence: 99%